Smart Home Appliance control system using Augmented reality technology. - Chai, Guo Qiang (2022)

(untitled)
Partially disabled and older adults need someone to take care of their daily routine, like reaching out for switches and home appliances. With the popularity of IoT and mobile devices, they can control their home appliances remotely. However, not everything is perfect in IoT control applications. User sacrifices their experience in controlling the physical switch. Therefore, this project regarding smart home appliances control systems using augmented reality technologies is proposed to overcome this problem. Augmented reality technologies bring virtual information to user’s immediate surroundings and any indirect view of the real-world environment. AR plays an essential role in this project to control home appliances. As the augmented reality trend grows gradually, people doubt whether they will control home appliances using augmented reality technology one day in the future. It is possible to achieve as nowadays some augmented reality-based home appliances control systems exist. However, it is not user-friendly, and the functions are also restricted. Therefore, a user-friendly AR controlled smart home appliances mobile application is developed to overcome three problems. First physical switches might be complicated for physically disabled or older adults to control. Second, a faulty or malfunctioning physical switch that has current leaking will harm users. Third, many IoT control applications are not user friendly but complicated. In a nutshell, this project aims to establish a user-friendly AR smart home appliance control application with a voice control function, far distance remote controlling and also short set-up time.